2012
DOI: 10.4093/dmj.2012.36.6.452
|View full text |Cite
|
Sign up to set email alerts
|

Education as Prescription for Patients with Type 2 Diabetes Mellitus: Compliance and Efficacy in Clinical Practice

Abstract: BackgroundDiabetes self-management education has an important role in diabetes management. The efficacy of education has been proven in several randomized trials. However, the status of diabetes education programs in real Korean clinical practice has not yet been evaluated in terms of patient compliance with the education prescription.MethodsWe retrospectively analyzed clinical and laboratory data from all patients who were ordered to undergo diabetes education during 2009 at Samsung Medical Center, Seoul, Kor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 18 publications
(21 reference statements)
0
11
0
Order By: Relevance
“…The lack of differences in health behaviour and glycaemic control between people with diabetes education and those without indicated that actual lifestyle modification to achieve glycaemic control and health benefits was not successfully accomplished after the education. These findings might reflect the content of education in the current health system in South Korea, which mostly comprises the concept of diabetes and diet management; generally, education does not incorporate behavioural or psychological strategies for diabetes management . Although detailed characteristics and the format of the diabetes education attended could not be examined in this study, the findings suggest that diabetes education has considerable room for improvement in the current health care system of South Korea.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The lack of differences in health behaviour and glycaemic control between people with diabetes education and those without indicated that actual lifestyle modification to achieve glycaemic control and health benefits was not successfully accomplished after the education. These findings might reflect the content of education in the current health system in South Korea, which mostly comprises the concept of diabetes and diet management; generally, education does not incorporate behavioural or psychological strategies for diabetes management . Although detailed characteristics and the format of the diabetes education attended could not be examined in this study, the findings suggest that diabetes education has considerable room for improvement in the current health care system of South Korea.…”
Section: Discussionmentioning
confidence: 85%
“…These findings might reflect the content of education in the current health system in South Korea, which mostly comprises the concept of diabetes and diet management; generally, education does not incorporate behavioural or psychological strategies for diabetes management. 19,20 Although detailed characteristics and the format of the diabetes education attended could not be examined in this study, the findings suggest that diabetes education has considerable room for improvement in the current health care system of South Korea. The inconsistency of our results with those from previous intervention studies showing the benefit of diabetes education on reducing HbA 1 C 4,11,21 could be explained by the highly diverse and unclear quality of diabetes education in clinical circumstances in South Korea.…”
Section: Discussionmentioning
confidence: 86%
“…Previous studies have suggested that several barriers are associated with diabetes education, including geographical distance, area of residence, cost issues, scheduling conflicts, feeling that education is unnecessary, health issues, and hearing impairments, 16 17 18 19) as well as being male, having a disability, and level of education. 20 21 22) However, the previous studies were based on surveys of diabetic patients or those who were involved in diabetes education and showed inconsistent results.…”
Section: Introductionmentioning
confidence: 99%
“…related goals is poor medication adherence (14). Non-adherence has been associated with poor clinical outcomes in diabetes and can influence the magnitude of the treatment effect (15,16). For instance, one study found that patients who were ≥ 80% adherent to their diabetes therapy, as measured by medication event monitoring systems, had lower follow-up HbA1c levels than those who were less adherent (17).…”
Section: Introductionmentioning
confidence: 99%